Upaya Meningkatkan Hasil Belajar Struktur Tubuh Manusia melalui Model Snowball Throwing Bagi Siswa SD - Hartini Hartini (Academy of Education Journal, 2018)
This research is motivated by the low learning outcomes of natural science subjects about the structure of the human body and its functions for fourth grade students of SD Negeri 2 Jatilawangsang odd semester 2014/2015 academic year. The purpose of this study is to improve student learning outcomes. The research was carried out through two cycles, namely through the first cycle and second cycle using the Snowball Throwing learning model. In the initial study the average value was 56.85, the first cycle being 72.85. Then in the second cycle increased optimally to 82.28. The percentage of completeness of the initial study was 25.71% then the first cycle became 77.15%. Then in the second cycle increased to 94.28%. The percentage of incomplete in the pre cycle 74.29% then the first cycle decreased to 22.85%. Then in the second cycle to 5.72%. Conclusion of the application of the Snowball Throwing model Improved Learning Outcomes of the Human Body Structure and Its Functions for Grade IV Students of SD Negeri 2 Sudagaran, Banyumas Regency 2014/2015 Academic Year.